Attrition in Randomized Controlled Trials for Pediatric Chronic Conditions - Karlson, Cynthia W.; Rapoff, Michael A. (Journal of pediatric psychology, 2009)
Objective To examine attrition variables in randomized controlled trials of cognitive behavioral interventions for children with chronic illnesses. Methods We examined attrition rates reported on 40 randomized cognitive behavioral interventions published in six pediatric research journals, during the years 2002–2007. Intervention focus was limited to children with a chronic medical condition, such as asthma, obesity, arthritis, diabetes, cancer, sickle cell disease, and cystic fibrosis. Results Mean rate of enrollment refusal was 37% (range 0–75%). Mean attrition rate was 20% (range 0–54%) for initial follow-up and 32% (range 0–59%) for extended follow-up. Of the reviewed articles, 40% included a CONSORT diagram. Conclusions Strategies that can be used to limit attrition include tailoring recruitment to the study population, providing personalized feedback, maintaining consistent study procedures, providing incentives, and using intensive tracking measures. There is a need for standardized definitions and reporting of attrition rates in randomized cognitive behavioral intervention studies.